(untitled) (Journal of Applied Learning and Teaching, 2023)
During the 2020 iteration of a Bachelor of Nursing Clinical Health Assessment skills course delivered in Singapore, the sudden cancellation of all face-to-face classes due to the COVID-19 pandemic resulted in innovative strategies being required and quickly created to enable students to successfully complete clinical skills laboratories and Objective Structured Clinical Examinations (OSCEs) online. However, the realism of the experience was rudimentary. At the end of the 2020 teaching semester, and the possibility that the next iteration of the course would also need to be online, it was decided to explore technologies to provide a more realistic and interactive user experience for the 2022 iteration of the Clinical Health Assessment skills course and particularly for the OSCEs. A research project was initiated in 2021, to develop and test the use of virtual or mixed reality applications for online simulated learning and clinical skills assessment. This paper discusses the development and operationalisation phases of a mixed reality interactive virtual patient application used for online OSCEs in a Clinical Health Assessment skills course.